2000
DOI: 10.1530/reprod/118.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ornidazole on fertility of male rats: inhibition of a glycolysis-related motility pattern and zona binding required for fertilization in vitro

Abstract: The effects of the male antifertility agent ornidazole on glycolysis as a prerequisite for fertilization were investigated in rats. Antifertility doses of ornidazole inhibited glycolysis within mature spermatozoa as determined from the lack of glucose utilization, reduced acidosis under anaerobic conditions and reduced glycolytic enzyme activity. As a consequence, cauda epididymidal spermatozoa from ornidazole-fed rats were unable to fertilize rat oocytes in vitro, with or without cumulus cells, which was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Although these observations would fit with the abundance of LDHC in these stages of spermatogenesis, there is no direct evidence to support this contention. On the other hand, it has been shown that glycolysable substrates are essential for sperm motility (Williams and Ford, 2001; Mukai and Okuno, 2004), for the protein tyrosine phosphorylation indicative of capacitation (Travis et al, 2001; Urner et al, 2001; Williams and Ford, 2001; Urner and Sakkas, 2003), and for fertilization (Urner and Sakkas, 1996; Bone et al, 2000). This was proven when inactivation of the gene for the sperm‐specific glycolysis pathway enzyme GAPDHS (Miki et al, 2004) dramatically reduced the level of adenosine triphosphate (ATP) in sperm, caused severe defects in progressive sperm motility and resulted in male infertility.…”
Section: Function(s) Of Ldhc Revealed (Or Not) By Its Absencementioning
confidence: 99%
“…Although these observations would fit with the abundance of LDHC in these stages of spermatogenesis, there is no direct evidence to support this contention. On the other hand, it has been shown that glycolysable substrates are essential for sperm motility (Williams and Ford, 2001; Mukai and Okuno, 2004), for the protein tyrosine phosphorylation indicative of capacitation (Travis et al, 2001; Urner et al, 2001; Williams and Ford, 2001; Urner and Sakkas, 2003), and for fertilization (Urner and Sakkas, 1996; Bone et al, 2000). This was proven when inactivation of the gene for the sperm‐specific glycolysis pathway enzyme GAPDHS (Miki et al, 2004) dramatically reduced the level of adenosine triphosphate (ATP) in sperm, caused severe defects in progressive sperm motility and resulted in male infertility.…”
Section: Function(s) Of Ldhc Revealed (Or Not) By Its Absencementioning
confidence: 99%
“…More recently, 1 H NMR studies in boar spermatozoa have found glycolytic pathways as important in maintaining a supply of lactate for mitochondrial ATP production [Jones and Bubb, 2000]. In other studies using ornidazole, a glycolysis inhibitor, 13 C labeled substrates coupled with 13 C NMR detection have been used to estimate glycolytic turnover suggesting that glycolysis supports hyperactivation as well as zona binding and penetration into spermatozoa [Bone et al 2000]. Gupta et al, [2011a, b] have used NMR spectroscopy to measure quantitatively the concentration of some metabolites and linear discriminant function analysis to determine the signature biomarkers and descriptors of infertility.…”
Section: Introductionmentioning
confidence: 99%
“…There appear to be some species differences in sperm metabolism (2), but previous in vitro studies reported that glycolysis is required for mouse (20)(21)(22), rat (23), and human sperm (24,25) to achieve hyperactivated motility and penetrate the zona pellucida during fertilization. The tyrosine phosphorylation of sperm proteins that occurs during acquisition of hyperactivated motility in vitro also depends upon glycolysis (26,27).…”
mentioning
confidence: 99%